Protective effects of elevated anandamide on stress and fear-related behaviors: translational evidence from humans and mice - Mayo, Leah M.; Asratian, Anna; Lindé, Johan; Holm, Lovisa; Nätt, Daniel; Augier, Gaëlle; Stensson, Niclas; Vecchiarelli, Haley A.; Balsevich, Georgia; Aukema, Robert J.; Ghafouri, Bijar; Spagnolo, Primavera A.; et al. (Molecular psychiatry, 2020)
Post-traumatic stress disorder (PTSD) is a common, debilitating condition with limited treatment options. Extinction of fear memories through prolonged exposure therapy, the primary evidence-based behavioral treatment for PTSD, has only partial efficacy. In mice, pharmacological inhibition of fatty acid amide hydrolase (FAAH) produces elevated levels of anandamide (AEA) and promotes fear extinction, suggesting that FAAH inhibitors may aid fear extinction-based treatments. A human FAAH 385C->A substitution encodes an FAAH enzyme with reduced catabolic efficacy. Individuals homozygous for the FAAH 385A allele may therefore offer a genetic model to evaluate the impact of elevations in AEA signaling in humans, helping to inform whether FAAH inhibitors have the potential to facilitate fear extinction therapy for PTSD. To overcome the challenge posed by low frequency of the AA genotype (appr. 5%), we prospectively genotyped 423 individuals to examine the balanced groups of CC, AC, and AA individuals ( n = 25/group). Consistent with its loss-of-function nature, the A allele was dose dependently associated with elevated basal AEA levels, facilitated fear extinction, and enhanced the extinction recall. Moreover, the A-allele homozygotes were protected against stress-induced decreases in AEA and negative emotional consequences of stress. In a humanized mouse model, AA homozygous mice were similarly protected against stress-induced decreases in AEA, both in the periphery, and also in the amygdala and prefrontal cortex, brain structures critically involved in fear extinction and regulation of stress responses. Collectively, these data suggest that AEA signaling can temper aspects of the stress response and that FAAH inhibition may aid the treatment for stress-related psychiatric disorders, such as PTSD.